Spodoptera frugiperda Smith fitness on four natural hosts using a two-sex life table in a controlled setting - Tajdar, Alia; Cao, Chuan; Jaleel, Waqar; Zaka, Syed Muhammad; Shi, Wangpeng (Frontiers in Insect Science, 2025)
Spodoptera frugiperda (J.E. Smith), (Noctuidae, Lepidoptera), commonly known as fall armyworm (FAW), is a significant polyphagous pest that can cause considerable damage to various crops. Fundamental research on FAW is crucial and beneficial for creating an integrated management strategy. Lot of literatures are available on web to describe the fitness of FAW via conventional methods that deals the basic biology of FAW. However, there is currently a need to check the fitness for each stage of FAW using an advanced two-sex life table tool, which is crucial for creating efficient control strategies. The proposed study used an age-stage, two-sex life table to examine the lifetable parameters of FAW on four natural hosts: castor beans (Ricinus communis), potatoes (Solanum tuberosum), maize (Zea mays L.), and wheat (Triticum aestivium L.). The findings demonstrated that, despite notable variations in development and reproduction, the FAW completed its life cycle on each of the four studied hosts. The FAW that were fed maize performed at their best, showing shorter immature (egg-pupa) phases, longer lifespans, and better rates of adult reproduction. On maize, female FAW had the highest fecundity (2497.1 eggs/female), while on wheat, it was the lowest (675 eggs/female). With values of 532.8 (offspring individual-1), 0.21d-1, and 1.23 d-1, respectively, net reproductive rate, intrinsic rate of increase, and finite rate of increase peaked on maize, while the corresponding parameters were lowest on wheat (94.62 offspring individual-1, 0.11 d-1, and 1.12 d-1, respectively). This study indicates that all host plants can contribute to the development and outbreak of this pest in the absence of its primary host. Therefore, all potential host plants in the area should be thoroughly examined when developing an IPM program against said pest.